High molecular gas content and star formation rates in local galaxies that host quasars, outflows, and jets. Issue 2 (9th September 2020) - Jarvis, M E; Harrison, C M; Mainieri, V; Calistro Rivera, G; Jethwa, P; Zhang, Z-Y; Alexander, D M; Circosta, C; Costa, T; De Breuck, C; Kakkad, D; Kharb, P; et al.
ABSTRACT: We use a sample of powerful $z\, ≈ \, 0.1$ type 2 quasars ('obscured'; log [ L AGN /erg s$^{-1}]\, \gtrsim \, 45$ ), which host kpc-scale ionized outflows and jets, to identify possible signatures of AGN feedback on the total molecular gas reservoirs of their host galaxies. Specifically, we present Atacama Pathfinder EXperiment (APEX) observations of the CO(2–1) transition for nine sources and the CO(6–5) for a subset of three. We find that the majority of our sample reside in starburst galaxies (average specific star formation rates – sSFR – of 1.7 Gyr −1 ), with the seven CO-detected quasars also having large molecular gas reservoirs (average M gas = 1.3 × 10 10 M⊙ ), even though we had no pre-selection on the star formation or molecular gas properties. Despite the presence of quasars and outflows, we find that the molecular gas fractions ( M gas / M ⋆ = 0.1–1.2) and depletion times ( M gas /SFR = 0.16–0.95 Gyr) are consistent with those expected for the overall galaxy population with matched stellar masses and sSFRs. Furthermore, for at least two of the three targets with the required measurements, the CO(6–5)/CO(2–1) emission-line ratios are consistent with star formation dominating the CO excitation over this range of transitions. The targets in our study represent a gas-rich phase of galaxy evolution with simultaneously high levels of star formation and nuclear activity; furthermore, the jets and outflows do not have an immediate appreciable impact on the global molecular gas reservoirs.